PETROLOGICAL CHARACTERS OF THE EARLY CRETACEOUS BOEOTHIAN FLYSCH, (CENTRAL GREECE) - Kyriakopoulos, K.; Karakitsios, V.; Tsipoura-Vlachou, M.; Barbera, G.; Mazzoleni, P.; Puglisi, D. (Bulletin of the Geological Society of Greece, 2010)
This paper is aimed to study the petrographic characters of the Boeothian Flysch, an Early Cretaceous turbidite deposit which marks the boundary between the External/Internal Hellenides in central-southern Greece, in order to define a preliminary palaeogeographic reconstruction of the Pindos segment of the Alpine Tethys. The Boeothian Flysch is mainly made up by basal conglomerates and arenaceous-pelitic lithofacies, locally interlayered with Calpionellid micrite limestones. This formation is here supposed to belong to the Early Cretaceous flysch family, which marks the contact between the internal and external areas along all the western and central European Alpine Chains for more than 7,000 km, from the Gibraltar Arc to the Balkans via the Calabria-Peloritani Arc. Provenance of these flysch is commonly connected to internal areas, mainly made up by Hercynian crystalline basements and, locally, by ophiolitic complexes. The petrographic data obtained from representative sandstones of the Boeothian Flysch suggest a provenance from internal sources, formed by a Jurassic carbonate platform, metamorphic basements and by ophiolitic complexes, which can be identified with the Pelagonian Terranes (Auct.). An Early Cretaceous uplift and rejuvenation processes, probably related to the late Cretaceous tectogenesis, widely recorded in almost all the central-western Alpine Tethis, affected these internal domains with consequent production of abundant detrital supply in the innermost sector of the Pindos Ocean, whose external margin was bounded by the Parnassos microcontinent.